Relationship between grammar and schizophrenia: a systematic review and meta-analysis - Dalia Elleuch; Yinhan Chen; Qiang Luo; Lena Palaniyappan (Communications Medicine)
Abstract Background Schizophrenia significantly impairs everyday communication, affecting education and employment. Such communication difficulties may arise from deficits in syntax—understanding and generating grammatical structures. Research on syntactic impairments in schizophrenia is underpowered, with inconsistent findings, and it is unclear if deficits are specific to certain patient subgroups, regardless of symptom profiles, age, sex, or illness severity. Methods A pre-registered (Open Science Framework: https://doi.org/10.17605/OSF.IO/7FZUC ) search using PubMed, Scopus, PsycINFO, and Web of Science databases up to May 1, 2024, for all studies investigating syntax comprehension and production in schizophrenia vs. healthy controls. Excluding studies on those <18 years of age and qualitative research, we extracted Cohen’s d and log coefficient of variation ratio and used Bayesian meta-analysis across 6 domains: 2 in comprehension and 4 in production in patient-control comparisons. Study quality was evaluated using a modified Newcastle–Ottawa Scale, with moderators (age, sex, study quality, language) tested via meta-regression. Results We identify 86 relevant articles, of which 45 have sufficient data for meta-analysis (n = 2960 participants, 64.4% English, weighted mean age(sd) = 32.3(5.6)). Bayesian meta-analysis shows strong evidence of syntactic deficits in schizophrenia across all domains (d = 0.65–1.01, overall random-effects d = 0.86, 95% CrI [0.67–1.03]), with syntax comprehension being most affected, with weak publication bias. People with schizophrenia show increased variability in comprehension and production of long and complex utterances (lnCVR = 0.21, 95% CrI [0.07–0.36]), hinting at subgroups with differing performance. Conclusions Robust impairments in grammatical comprehension and production in schizophrenia suggest opportunities for targeted interventions focusing on syntax, a rule-based feature amenable to cognitive, educational, and linguistic interventions.